A Lipidomics Approach to Assess the Association Between Plasma Sphingolipids and Verbal Memory Performance in Coronary Artery Disease Patients Undertaking Cardiac Rehabilitation: A C18:0 Signature for Cognitive Response to Exercise. - Saleem, Mahwesh; Herrmann, Nathan; Dinoff, Adam; Mielke, Michelle M; Oh, Paul I; Shammi, Prathiba; Cao, Xingshan; Venkata, Swarajya Lakshmi Vattem; Haughey, Norman J; Lanctôt, Krista L (J Alzheimers Dis, 2017)
BACKGROUND: Early subtle deficits in verbal memory, which may indicate early neural risk, are common in patients with coronary artery disease (CAD). While exercise can improve cognition, cognitive response to exercise is heterogeneous. Sphingolipids have been associated with the development and progression of CAD, and impairments in sphingolipid metabolism may play roles in neurodegeneration and in the neural adaptation response to exercise. OBJECTIVE: In this study, change in plasma concentrations of sphingolipids was assessed in relation to change in verbal memory performance and in other cognitive domains among CAD subjects undertaking a 6-month cardiac rehabilitation (CR) program. METHODS: Patients with CAD (n = 120, mean age = 64±6 y, 84% male, years of education = 16±3) underwent CR with neuropsychological assessments and blood collected at baseline, 3-, and 6-months. Z-scores based on age, gender, and education were combined for verbal memory, visuospatial memory, processing speed, executive function, and global cognition tasks to calculate cognitive domain Z-scores. Plasma sphingolipid concentrations were measured from fasting blood samples using high performance liquid chromatography coupled electrospray ionization tandem mass spectrometry (LC/MS/MS). Mixed models were used to identify sphingolipids significantly associated with performance in verbal memory and other cognitive domains, adjusting for potential confounders. RESULTS: A decrease in ceramide C18:0 concentration was significantly associated with improvement in verbal memory performance (b[SE] = -0.51 [0.25], p = 0.04), visuospatial memory (b[SE] = -0.44 [0.22], p = 0.05), processing speed (b[SE] = -0.89 [0.32], p = 0.007), and global cognition (b[SE] = -1.47 [0.59], p = 0.01) over 6 months of CR. CONCLUSIONS: Plasma ceramide C18:0 concentrations may be a sensitive marker of cognitive response to exercise in patients with CAD.